IRON ADSORPTION IN PEAT WATER BY SAGO WASTE ACTIVATED CARBON - Awali Sir Kautsar Harivram; Isna Syauqiah; Muthia Elma; Erdina Lulu Atika Rampun; Dina Amryna Chairul Putri; Namira Ghina Safitri (Universitas Lambung Mangkurat, 2022)
In South Kalimantan, peat water is the main water sources for local people. But peat water has high iron content. It cannot be consumed directly and need further treatment. Adsorption is the most common technology to treat peat water. The goal of this research is to study sago waste adsorbent for iron removal in peat water. Citric acid was employed as activating agent in the sago waste activated carbon adsorbent fabrication. Carbonization process was done at 300 ℃ with 70, 80, 90, 100, 110 and 120 minutes of time variation. After treatment using the adsorbent, iron content was tested via Atomic Absorption Spectrophotometry (AAS). While, Fourier Transform Infra-Red (FTIR) were carried out to investigate the functional groups of sago pith waste activated carbon (SPWAC) and sago pith waste unactivated carbon (SPWUC). The experiment results show iron could be removed until 82% with iron concentration of 0.05 mg/l at 80 minutes. SPWAC and SPWUC have functional groups such as alkenes (C-H and C=C), carbonyl (C=O and C-O) and hydroxyl (O-H). Fe concentrations are still meet water quality standard according to No. 492/Menkes/PER/IV/2010 which is 0.3 mg/L. Therefore, adsorption uses sago pith waste activated carbon is an effective and inexpensive water treatment.